2013
DOI: 10.1021/ed4000102
|View full text |Cite
|
Sign up to set email alerts
|

A Process for Developing Introductory Science Laboratory Learning Goals To Enhance Student Learning and Instructional Alignment

Abstract: Learning goal (LG) identification can greatly inform curriculum, teaching, and evaluation practices. The complex laboratory course setting, however, presents unique obstacles in developing appropriate LGs. For example, in addition to the large quantity and variety of content supported in the general chemistry laboratory program, the interests of faculty members from various chemistry subdisciplines and the service goals of such a course should be addressed. To optimize the instructional impact of limited labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 17 publications
0
21
0
Order By: Relevance
“…To address the first and second research questions, the prevalence of goal statements made by students is displayed in Table . Less than half of the students viewed lab as a place to apply critical thinking skills, integrate information from other coursework, or generate conceptual knowledge, even though these goals all rank high among chemistry faculty members’ stated purposes for laboratory coursework (Bretz, Fay, Bruck, & Towns, ; Bruck & Towns, ; Duis et al, ). Another goal on which students and faculty agreed was the cooperative work between laboratory partners ( n = 11, 65%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To address the first and second research questions, the prevalence of goal statements made by students is displayed in Table . Less than half of the students viewed lab as a place to apply critical thinking skills, integrate information from other coursework, or generate conceptual knowledge, even though these goals all rank high among chemistry faculty members’ stated purposes for laboratory coursework (Bretz, Fay, Bruck, & Towns, ; Bruck & Towns, ; Duis et al, ). Another goal on which students and faculty agreed was the cooperative work between laboratory partners ( n = 11, 65%).…”
Section: Resultsmentioning
confidence: 99%
“…The interviews were coded using QSR International's NVivo 10 Software (QSR, ). The codes were initially generated from a previously published list of laboratory goals that were generated by science faculty and discipline based education researchers (Duis, Schafer, Nussbaum, & Stewart, ), with additional codes created for unique goals that were introduced by students during the interviews. (A complete list of codes is available as supplementary material accompanying the online article.)…”
Section: Methodsmentioning
confidence: 99%
“…The rest of the elements are showing the value of κ approaching the value of 1 which means the assessor reaches the consent of the assessors. The finding showed that the process of developing a practical learning also need technologies to achieve the goals in learning, especially in improving student's hands-on skills such as handle machines, tools or programming software which will enhanced their technical skills (Duis et al, 2013). According to Nikolic (2014), the practical learning also gives students an opportunity to use technologies for gaining experience in scientific tools, results analysis, conducting experiments and find a solution to get actual finding.…”
Section: Content Knowledgementioning
confidence: 99%
“…The importance of learning from high quality laboratory curriculum (5,30) is also something the authors want to investigate with practice exam data.…”
mentioning
confidence: 99%